Perlindungan Perlindungan Terhadap Perempuan Korban Kekerasan Berbasis Gender Online Dalam Era Digital - Ni Nyoman Muryatini (Fakultas Hukum, Universitas Warmadewa, 2024)
In today’s digital era, sexual violence crimes often occur in cyberspace. Based on the annual records of the National Commission on Violence Against Women, reports of cases of online gender-based violence have increased in the last five years. Cyberspace is currently not a safe space for women. As a basic law, the Indonesian Constitution of 1945 explicitly regulates the right to a sense of security and protection for everyone. The methods used in this study are normative juridical using a legislative approach and a case approach. The purpose of this study is to provide legal arguments regarding whether an event is right or wrong and how the event should be according to law. Based on the results of the study, in law enforcement, law enforcement officers often use the electronic information and transactions law and the pornography law which results in victims being in a vulnerable position. The negative stigma from society and criminalization of victims result in a minimum of cases being resolved through litigation so that victims do not get the right to handling and recovery as mandated by the law on sexual violence. The state must guarantee a safe space for women in cyberspace. The state must carry out its commitment to provide justice and restitution to victims as mandated by law. For the sake of legal certainty, the government must immediately ratify the implementing regulations of the law on sexual violence. Provide socialization to the public regarding the law on sexual violence to increase public legal awareness and improve the competence of law enforcement officers by providing training in handling cases of online gender-based violence.